Build it so they can play affordable equipment for adapted physical education - Sullivan, Teresa 1972-; Slagle, Cindy; Hapshie, T.J; Brevard, Debbie (Human Kinetics, 2012)
Let's make some fun! Now you can create low-cost physical education equipment from everyday items and inexpensive building supplies with Build It So They Can Play: Affordable Equipment for Adapted Physical Education. Physical education teachers, caregivers, and play group and recreation leaders can use Build It So They Can Play to construct a wealth of creative and adaptable physical education equipment to fit any budget! In this book, you'll find ideas for equipment to modify participation in typical sports and recreation activities; encourage vestibular and fine motor development; provide audio, visual, and tactile stimulation; and find additional ideas for use and suggestions for customizing the equipment for various abilities and purposes. Every equipment project, from the simplest to the most involved, has been field tested to ensure success by the author team of veteran adapted physical educators. Step-by-step instructions, diagrams, detailed photos, and lists of necessary tools and materials help you stay organized and save time! Tight budgets can be a challenge-don't let them become a limitation. With Build It So They Can Play, you can help students discover new ways to enjoy and benefit from physical activity, regardless of your budget. Grab this book, get your tool belt, and build some fun!--Book jacket.